Pengaruh Label Halal, Religious Commitment, Brand Ambassador Dan Desin Produk Terhadap Keputusan Pembelian Kosmetik Wardah Studi Pada Mahasiswa Universitas Muhammadiyah Metro - Lestari, Anik; Septiana, Nani (Jurnal Manajemen DIVERSIFIKASI, 2021)
Wardah is one of Indonesia's local products, a cosmetic product from PT Paragon Technology and Innovation. Wardah is one of the first cosmetics to guarantee halal cosmetic products. Wardah is even able to compete and develop to beat previous products to become one of the superior local products by displaying product advantages and Wardah having a consultant on every sale to attract buyers to make repeat purchases. Even Wardah product designs are created as attractive as possible to influence consumers to make purchasing decisions. This study aims to determine the effect of the halal label, religious commitment, brand ambassador, and product design on purchasing decisions for Wardah cosmetics. This research method is quantitative using the explanatory research method. It is used to examine the population or sample. The sampling technique is generally carried out randomly, namely the Muhammadiyah University Metro students, with a sample size of 40 people. The data analysis techniques used are validity test, reliability test, normality test, linearity test, testing. The analysis method in this research uses multiple linear regression analysis, test, test, and R2 test of determination. Based on the results of the study using the t-test, it was found that the Halal Label has a positive and significant effect on Wardah Cosmetics Purchase Decisions, Religious Commitment has a positive and significant effect on Wardah Cosmetics Purchase Decisions, Brand Ambassador has a positive and significant effect on Wardah Cosmetics Purchase Decisions. Significant towards Wardah cosmetic purchasing decisions. Based on the analysis of SPSs data, the conclusion of the halal label, religious commitment, brand ambassador, and product design has a positive and significant effect on purchasing Wardah cosmetics.Keywords: Halal Label, Religious Commitment, Brand Ambassador, Product Design and Purchase Decision